Adult Day Service Providers: Untapped Potential for Care Coordination - Nicole Ruggiano; Ellen L. Brown; Karen L. Fortuna (Nursing & Health Sciences Research Journal, 2018)
Adult Day Services (ADS) have become increasingly available for community-dwelling older adults who are often experiencing multiple chronic conditions and/or dementia. ADS providers spend a significant amount of time with their clients and offer the opportunity for a wealth of clinical information that can be used by primary care providers and specialists for decision-making about patient care. There are also opportunities for hospitals to coordinate care transitions with ADS providers by involving them with discharge planning with appropriate patients who require post-hospital care. However, ADS providers are often viewed as social service providers, and there is little known about the role they can and do play as part of clinical care coordination teams. This paper reviews the current state of practice, policy, and research on ADS providers and evaluates the benefits and challenges to increasing their involvement in the health care of older adults.